CATALYTIC PERFORMANCE OF DESILICATED HZSM-12 FOR BENZYLATION REACTION OF BENZENE WITH BENZYL ALCOHOL: Original scientific paper - Akyalcin, Sema; Akyalcin, Levent; Bjørgen, Morten (Chemical Industry & Chemical Engineering Quarterly, 2023)
The catalytic production of diphenylmethane from the reaction of benzene with benzyl alcohol was investigated using HZSM-12 and desilicated HZSM-12 that was obtained by treating ZSM-12 with 0.2M NaOH solution at 85 °C for 60 min. The untreated and alkaline treated ZSM-12 zeolites were characterized by X-ray diffraction, nitrogen adsorption/desorption isotherms, scanning electron microscopy, inductively coupled plasma optical emission spectrometry, and temperature-programmed desorption of ammonia. The desilicated HZSM-12 showed promising catalytic performance with benzyl alcohol conversion of 100% and the selectivity to diphenylmethane of 74% and 87% in 4 h and 8 h reaction time, respectively. The reaction parameters affecting benzyl alcohol conversion and product distribution were also presented. The activities of fresh and regenerated catalysts were compared, and characterization results indicated that the occluded organic molecules decreased the number of acidic sites of the catalyst after the reaction and regeneration.